Cancer risk among Holocaust survivors in Israel—A nationwide study. Issue 17 (10th July 2017) - Sadetzki, Siegal; Chetrit, Angela; Freedman, Laurence S.; Hakak, Nina; Barchana, Micha; Catane, Raphael; Shani, Mordechai
Abstract : BACKGROUND: Holocaust survivors during World War II were exposed to various factors that are associated with cancer risk. The objective of this study was to determine whether Holocaust survivors had an increased risk for developing cancer. METHODS: The study population included 152, 622 survivors. The main analysis was based on a comparison between individuals who were entitled to compensation for suffering persecution during the war and individuals who were denied such compensation. A complementary analysis compared survivors who were born in countries governed by Nazi Germany with survivors born in nonoccupied countries. A Cox proportional hazards model was used, with the time at risk of cancer development starting on either January 1, 1960, or the date of immigration to the date of cancer diagnosis or death or the date of last follow‐up (December 31, 2006). RESULTS: Cancer was diagnosed in 22.2% of those who were granted compensation versus 16% of those who were denied compensation ( P < .0001). Adjusting for birth cohort, sex, country of origin, and period of immigration, both analyses revealed significant increased risks of developing cancer in those who were exposed. For those who were granted versus denied compensation, the hazard ratios were 1.06 ( P < .001) for all sites, 1.12 ( P = .07) for colorectal cancer, and 1.37 ( P = .008) for lung cancer. For those born in occupied countries versus nonoccupied countries, the hazard ratios were 1.08 ( P < .001), 1.08 ( P = .003), and 1.12 ( P = .02), respectively. CONCLUSIONS: The current results, based on a large cohort of Holocaust survivors who were exposed to a variety of severe deprivations, add to the conflicting and sparse knowledge on this issue and support the notion that this group has a small but consistent increase in cancer development. Cancer 2017;123:3335‐45 . © 2017 American Cancer Society . Abstract : On the basis of a nationwide cohort of Holocaust survivors who were exposed to various severe and protracted personal deprivations, cancer is diagnosed among 22.2% of survivors compared with 16% of a comparison group ( P < .0001), and an excess risk is demonstrated for all cancer sites and for lung and colorectal cancers. The results add to the conflicting and sparse knowledge on this issue and support the notion that survivors of the Holocaust have a small but consistent increase in cancer risk. See also pages 3226‐8.